A Glycan Array‐Based Assay for the Identification and Characterization of Plant Glycosyltransferases. Issue 30 (3rd June 2020) - Ruprecht, Colin; Bartetzko, Max P.; Senf, Deborah; Lakhina, Anna; Smith, Peter J.; Soto, Maria J.; Oh, Hyunil; Yang, Jeong‐Yeh; Chapla, Digantkumar; Varon Silva, Daniel; Clausen, Mads H.; Hahn, Michael G.; et al.
Abstract: Growing plants with modified cell wall compositions is a promising strategy to improve resistance to pathogens, increase biomass digestibility, and tune other important properties. In order to alter biomass architecture, a detailed knowledge of cell wall structure and biosynthesis is a prerequisite. We report here a glycan array‐based assay for the high‐throughput identification and characterization of plant cell wall biosynthetic glycosyltransferases (GTs). We demonstrate that different heterologously expressed galactosyl‐, fucosyl‐, and xylosyltransferases can transfer azido‐functionalized sugar nucleotide donors to selected synthetic plant cell wall oligosaccharides on the array and that the transferred monosaccharides can be visualized "on chip" by a 1, 3‐dipolar cycloaddition reaction with an alkynyl‐modified dye. The opportunity to simultaneously screen thousands of combinations of putative GTs, nucleotide sugar donors, and oligosaccharide acceptors will dramatically accelerate plant cell wall biosynthesis research. Abstract : Express and screen : A high‐throughput assay based on the application of azido‐functionalized sugar nucleotide donors on a synthetic glycan array for screening heterologously expressed plant glycosyltransferases was developed. The opportunity to express and screen large numbers of glycosyltransferases instead of rationally selected candidates will markedly accelerate the elucidation of plant cell wall biosynthetic pathways.